Association Between Echocardiography Laboratory Accreditation and the Quality of Imaging and Reporting for Valvular Heart Disease. (August 2017) - Thaden, Jeremy J.; Tsang, Michael Y.; Ayoub, Chadi; Padang, Ratnasari; Nkomo, Vuyisile T.; Tucker, Stephen F.; Cassidy, Cynthia S.; Bremer, Merri; Kane, Garvan C.; Pellikka, Patricia A.
Abstract : Background—: It is presumed that echocardiographic laboratory accreditation leads to improved quality, but there are few data. We sought to compare the quality of echocardiographic examinations performed at accredited versus nonaccredited laboratories for the evaluation of valvular heart disease. Methods and Results—: We enrolled 335 consecutive valvular heart disease subjects who underwent echocardiography at our institution and an external accredited or nonaccredited institution within 6 months. Completeness and quality of echocardiographic reports and images were assessed by investigators blinded to the external laboratory accreditation status and echocardiographic results. Compared with nonaccredited laboratories, accredited sites more frequently reported patient sex (94% versus 78%; P <0.001), height and weight (96% versus 63%; P <0.001), blood pressure (86% versus 39%; P <0.001), left ventricular size (96% versus 83%; P <0.001), right ventricular size (94% versus 80%; P =0.001), and right ventricular function (87% versus 73%; P =0.006). Accredited laboratories had higher rates of complete and diagnostic color (58% versus 35%; P =0.002) and spectral Doppler imaging (45% versus 21%; P <0.0001). Concordance between external and internal grading of external studies was improved when diagnostic quantification was performed (85% versus 69%; P =0.003), and in patients with mitral regurgitation, reproducibility was improved with higher quality color Doppler imaging. Conclusions—: Accredited echocardiographic laboratories had more complete reporting and better image quality, while echocardiographic quantification and color Doppler image quality were associated with improved concordance in grading valvular heart disease. Future quality improvement initiatives should highlight the importance of high-quality color Doppler imaging and echocardiographic quantification to improve the accuracy, reproducibility, and quality of echocardiographic studies for valvular heart disease.